Ultrasound and glycosylation modifications enhance the physicochemical and functional properties of canola protein isolate for O/W emulsion stabilization - Ziqin Ye; Jinying Wang; Guilan Ma; Jinge Ma (Food Chemistry: X)
This study aimed to prepare different modified canola protein isolates (CPIs), including ultrasound (U), glycosylation (G), ultrasound-glycosylation (U-G), and glycosylation-ultrasound (G-U). Assess the effect of different modifications on the quality characteristics of CPIs and the ability to stabilize emulsions. Sonication was found to increase the surface hydrophobicity resulting from the unfolding structure of CPI. The dual-modified U-G-CPI with 27.69 % glycosylation showed a solubility of 90.26 %, and an emulsification capacity of 80.87 m2/g. The emulsions stabilized by U-G-CPI exhibited higher degrees of protein adsorption (84.56 %) and a smaller particle size (4.22 μm) with a more homogeneous distribution at the oil-water interface. Additionally demonstrated enhanced thermal and salt stability resulting from its increased surface hydrophobicity and net charge. Overall, the ultrasound combined with glycosylation modification was found to significantly improve both the stability and emulsification properties of CPI, highlighting its potential as a plant-based emulsifier in the food sector and beyond.